2005
DOI: 10.1021/bi048198d
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Phosphonate Analogues of the Tetrahedral Reaction Intermediate with 5-Enolpyruvylshikimate-3-phosphate Synthase in Atomic Detail,

Abstract: The enzyme 5-enolpyruvylshikimate-3-phosphate synthase (EPSPS) catalyzes the penultimate step of the shikimate pathway and is the target of the broad-spectrum herbicide glyphosate. Since the functionality of the shikimate pathway is vital not only for plants but also for microorganisms, EPSPS is considered a prospective target for the development of novel antibiotics. We have kinetically analyzed and determined the crystal structures of Escherichia coli EPSPS inhibited by (R)- and (S)-configured phosphonate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
36
0

Year Published

2005
2005
2025
2025

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 36 publications
2
36
0
Order By: Relevance
“…EPSPS was identified as the target of the mostly used herbicide glyphosate [4]. Glyphosate mimics the carbocation state of PEP and binds to the binding site of PEP, forming a dead end EPSPS-S3P-glyphosate ternary complex [5][6][7] and thus blocking the formation of EPSP.…”
Section: Introductionmentioning
confidence: 99%
“…EPSPS was identified as the target of the mostly used herbicide glyphosate [4]. Glyphosate mimics the carbocation state of PEP and binds to the binding site of PEP, forming a dead end EPSPS-S3P-glyphosate ternary complex [5][6][7] and thus blocking the formation of EPSP.…”
Section: Introductionmentioning
confidence: 99%
“…Several of our attempts to identify the cation binding site(s) by cocrystallization of the unliganded or S3P-liganded states of the enzyme with the more electron-dense Rb ϩ ion failed. It is conceivable, however, that monovalent cations may bind transiently to the enzyme, acting as chaperones in restructuring the loop, enabling CP4 EPSP synthase to interact more efficiently with PEP during a catalytic cycle (20). Once the loop has adopted a regular structure, the cation-binding site(s) may be lost.…”
mentioning
confidence: 99%
“…Crystallographic and chemical studies using E. coli EPSPS demonstrated the 2-(S)-configuration of the TI (20,21). The mode of action of glyphosate on EPSPS is well understood (22,23), but intensive efforts to find a molecule better than glyphosate at inhibiting class I EPSPS have largely failed; only a few analogues of the TI have been identified as more potent inhibitors (11,24,25). The molecular modes of action of the (R)-and (S)-phosphonate TI analogues (RP-TI and SP-TI, respectively) on E. coli EPSPS were determined recently by X-ray crystallography and indicated that this enzyme may facilitate the tight binding of such inhibitors through conformational flexibility (25).…”
mentioning
confidence: 99%